Extrapyramidal Side Effects in a Patient with Alcohol Withdrawal Symptoms: A Reflection of Quality of the Mental Health Care System - Kaggwa, Mark Mohan; Nkola, Rahel; Najjuka, Sarah Maria; Bongomin, Felix; Ashaba, Scholastic; Mamun, Mohammed A (Risk Management and Healthcare Policy, 2021)
Background: The burden of substance use disorders is increasing in most countries in sub- Saharan Africa. Individuals with substance use disorders (eg, alcohol use disorder) are at high risk of manifesting extrapyramidal side effects or extrapyramidal symptoms (EPS) during treatment of alcohol-induced mental illness symptoms especially psychosis. EPS management poses a challenge since some of the drugs used for treating EPS have addictive properties. The knowledge about EPS diagnosis and treatment is not well distributed across the health system, with health workers at lower health facilities having least awareness. The present case gives details of a patient who developed EPS during the management of alcohol withdrawal symptoms. Case Details: Following cessation of alcohol use, a 54-year-old man with alcohol use disorder presented with a one-week history of visual, auditory and tactile hallucinations, illusions, insomnia, extreme fear and irritability. He was managed with several daily doses of intramuscular chlorpromazine 100 mg, whenever he woke up aggressive from sedation from a peripheral health facility. Four days after his admission, he became mute, stiff, immobile, triple-flexed, tremulous and was drooling saliva. He was referred to a secondary facility for further management while on antipsychotic medication. Finally, he was referred to a tertiary facility, managed with tablets of benzhexol 5 mg twice daily and intravenous diazepam 20 mg per day. Daily follow-up was done using the extrapyramidal symptom rating scale (ESRS) for EPS. EPS symptoms resolved ten days after initiation of treatment. Conclusion: EPS among individuals with addictive disorders poses a challenge in its management, especially in countries where the mental health care system is not well developed at lower-level health facilities. The mental health system has to prepare sustainable interventions to properly manage EPS among the growing population of individuals with addictive disorders through strengthening the mental health policy by training and equipping all health providers with knowledge and skills in managing EPS, increasing finances allocated for mental health and controlling the production and use of addictive substances.
Keywords: Extrapyramidal side effects; Typical antipsychotics; Mental health system; Addiction, alcohol use disorder; EPS; Withdrawal symptoms; Akandi; Uganda